The Use of Semantic Lexical Relation in Rowlingâ€™s â€œHarry Potter and the Deathly Hallowsâ€ - Setianingrum, Diah Ayu; Mujiyanto, Januarius; Fitriati, Sri Wuli (Universitas Negeri Semarang, 2021)
Semantics is the study of wordsâ€™ meaning. One of the branches of semantics is a lexical relation study. It refers to the relationship between the meaning of words. The focus of this article is the explanation of the use of three types of lexical relations: synonymy, antonymy and hyponymy in the Rowlingâ€™s novel â€œHarry Potter and the Deathly Hallowsâ€. The study aims to explain the use of the elements or the three types of semantics lexical relation appeared in that novel.This study employed qualitative research in the form of content analysis which deeply investigates the meanings in the novel. The units of analysis are words that appeared in the novel, taken from the whole chapters of the novel. Therefore, the object is semantics lexical relations comprising three types of lexical relations: synonymy, antonymy and hyponymy.The findings show that each type of lexical relation is interconnected with one another. The most dominant type that is used by the author of the novel is antonymy. There were 148 out of 319 items, followed by synonymy with 97 finding items and then hyponymy with 26 finding items.This current study hopefully can enhance the teacher or lecturers and the students English Language Education to involve the semantics lexical relation. Moreover, the findings and discussions can be applied in English Language Education Study Program, specifically in the semantics subject. The implications of lexical relation could be found not only in an English textbook but also in literature work such as novel, poetry, poem, even in play or drama, which is the subject that is required to learn by every single student.